Multi-layered bulk product filling material - Wood Brian (2017)
A filling product comprising a plurality of narrow, elongated strip segments is provided. Each strip segment has a plurality of transverse folds and substantially planar portions between adjacent folds. At least some of the strip segments comprise at least two layers of material, including a first layer comprising a first material and a second layer comprising a second material, wherein the second material is different in composition from the first material. Corresponding methods of producing such filling products are also provided.